Maternal and neonatal outcomes after implementation of a hospital policy to limit low‐risk planned caesarean deliveries before 39 weeks of gestation: an interrupted time‐series analysis. (8th April 2015) - Hutcheon, JA; Strumpf, EC; Harper, S; Giesbrecht, E
<x xml:space="preserve">Abstract</x> Objective To evaluate the extent to which implementing a hospital policy to limit planned caesarean deliveries before 39 weeks of gestation improved neonatal health, maternal health, and healthcare costs. Design Retrospective cohort study. Setting British Columbia Women's Hospital, Vancouver, Canada, in the period 2005–2012. Population Women with a low‐risk planned repeat caesarean delivery. Methods An interrupted time series design was used to evaluate the policy to limit planned caesarean deliveries before 39 weeks of gestation, introduced on 1 April 2008. Main outcome measures Composite adverse neonatal health outcome (respiratory morbidity, 5‐minute Apgar score of <7, neonatal intensive care unit admission, mortality), postpartum haemorrhage, obstetrical wound infection, out‐of‐hour deliveries, length of stay, and healthcare costs. Results Between 2005 and 2008, 60% (1204/2021) of low‐risk planned caesarean deliveries were performed before 39 weeks of gestation. After the introduction of the policy, the proportion of planned caesareans dropped by 20 percentage points (adjusted risk difference of 20 fewer cases per 100 deliveries; 95% CI −25.8, −14.3) to 41% (1033/2518). The policy had no detectable impact on adverse neonatal outcomes (2.2 excess cases per 100; 95% CI −0.4, 4.8), maternal complications, or healthcare costs, but increased the risk of out‐of‐hours delivery from 16.2 to 21.1% (adjusted risk difference 6.3 per 100; 95% CI 1.6, 10.9). Conclusions We found little evidence that a hospital policy to limit planned caesareans before 39 weeks of gestation reduced adverse neonatal outcomes. Hospital administrators intending to introduce such policies should anticipate, and plan for, modest increases in out‐of‐hours and emergency‐timing.